Assessment of the apical transportation and quantity of root canal dentin removed using different new rotary file systems: An original study - Harmeet Singh; Anuj K Shukla; Apurva A Jadhav; Anshuman Shetty; Chitharanjan Shetty; Smita D Dutta; Mohammed Mustafa (Wolters Kluwer Medknow Publications, 2023)
Introduction: The rotary systems have found a common application in the clinical practice for the endodontic therapies. Hence, we compared three recent endodontic systems for the comparison of the dentine removal and the apical transportation particularly in the curved canals. Methods: Oneshape, Pro Taper Next, and Edgefile X3 were the three systems that were compared. Thirty maxillary mesio buccal canals of the human permanent teeth were compared due to its curved nature. The volume of dentin removed and apical transportation (mm) were measured using micro-computed tomographic imaging (mm). Both the coronal section and the entire canal length had their dentin removed in accordance with measurements. Total dentine removed, coronal dentine removed, and the canal transportations were compared for the three rotary file systems. The values were compared with appropriate statistical tests for evaluating the significance. Results: There was no statistically significant difference between the three file systems for the dentin removed. The mean canal transportation was 0.33 ± 0.12, 0.21 ± 0.25, and 0.23 ± 0.21 mm, respectively, for Oneshape, Pro Taper Next, and Typhoon CM. In terms of statistics, there were no appreciable variations among the three rotary tools for apical transfer. Conclusions: The three rotary systems were comparable for the apical transportation and the dentine removal. Despite variations in the magnitude of apical enlargements, none of the instrumentation methods detected apical transportation.